2017
DOI: 10.1177/0047287517706263
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Smartphones on the Family Vacation Experience

Abstract: Families seek vacations as a means to improve family interaction and cohesion. Research on the effects of smartphones and other technology on the tourist experience has gained traction in recent years. Unfortunately, there still remains a void in understanding the role smartphones have on interaction and relationship dynamics during family vacations. Therefore, a qualitative research approach was employed to understand the extent to which smartphone usage influences the family vacation experience. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 73 publications
(87 reference statements)
3
40
0
2
Order By: Relevance
“…With regard to theoretical approaches, our data confirm both the hypothesis of the negative impact of the media on the family life and also its positive benefits (e.g. Padilla-Wlker et al 2012;Torrecillas-lava et al 2017;Yu et al 2018). Note: The numbers in bold are the most significant discussed later in the text…”
Section: Media Activities As Part Of Spending Leisure Timesupporting
confidence: 85%
See 1 more Smart Citation
“…With regard to theoretical approaches, our data confirm both the hypothesis of the negative impact of the media on the family life and also its positive benefits (e.g. Padilla-Wlker et al 2012;Torrecillas-lava et al 2017;Yu et al 2018). Note: The numbers in bold are the most significant discussed later in the text…”
Section: Media Activities As Part Of Spending Leisure Timesupporting
confidence: 85%
“…Moreover, most of the participants reported that their partner ignores them and their children due to excessive time spent on Facebook." (Ünal 2018, 362) Another modern electronic medium was studied by Yu et al (2018), which pointed out at the role of smartphones in the field of family leisure time and, above all, at the level of common holidays. Leisure time is precisely what the family can use to improve family interaction and cohesion.…”
Section: Media Research In the Context Of Family Issuesmentioning
confidence: 99%
“…Para além de contribuírem para a experiência turística dos turistas, da sustentabilidade dos destinos e devido às suas características que permitem um ambiente colaborativo (Christino, Silva, Cardozo & Lopes, 2019), permitem melhorar a interação e a coesão familiar durante todas as etapas de uma viagem (Yu et al, 2018), que reforçam um sentido de união dentro do grupo familiar, que contribui para o bem-estar dos viajantes, enquanto mantêm a sua individualidade e vão ao encontro das suas preferências, bem como são um suporte para gestão e manutenção das memórias associadas à experiência turística.…”
Section: Smart Travelunclassified
“…O smartphone é cada vez mais um complemento de viagem, sendo considerando um acessório essencial. Este estudo permitiu concluir que os turistas recorrem a este tipo de dispositivo para consultar informação sobre os destinos e os pontos de interesse existentes ao longo do percurso da sua viagem, bem como recorrem a esta tecnologia para efetuar reservas e comunicar com amigos, familiares e outros viajantes, tal no estudo de Braga (2015), Wang et al (2012;, Yu et al (2018), entre outros. Uma das redes sociais mais utilizada é o TripAdvisor, seguindo-se o Google+ e o Facebook, para consultar informação sobre destinos turistiscos e seus pontos de interesse, bem como fotografias e comentários, tal como no estudo de Xiang e Gretzel (2010).…”
Section: Considerações Finaisunclassified
“…to restore day and night, work and rest, learn the discipline of digitally disconnecting" (Global Wellness Summit, 2017, p.35). Technology such as smartphones can, however, enhance a vacation experience and foster family relationships, increase engagement and interaction while at a destination and also support recollection of memories (Yu, Anaya, Miao, Lehto & Wong, 2017). Even in the midst of technological advancements, the notions of wellness, restoration and transformation will increasingly be associated with tourism encounters.…”
Section: Thesis Backgroundmentioning
confidence: 99%